2013
DOI: 10.1055/s-0032-1317946
|View full text |Cite
|
Sign up to set email alerts
|

A Stereoselective Approach to (Z)-1-Silyl-2-aryl-1,3-dienes from 4-(Phenylselanyl)but-1-yne via Palladium-Catalyzed Silylstannylation and Selenoxide Elimination

Abstract: The palladium-catalyzed silylstannylation of 4-(phenylselanyl)but-1-yne proceeded regio-and stereoselectively, followed by selenoxide elimination via oxidation to give (Z)-1-(trimethylsilyl)-2-(tributylstannyl)buta-1,3-diene in good yield. This conjugated diene underwent the Stille coupling reaction with various aryl iodides in the presence of Pd(PPh 3 ) 4 to afford (Z)-2-aryl-1-(trimethylsilyl)buta-1,3-dienes with high stereoselectivity. Reversing the order of selenoxide elimination and Stille coupling reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Segi and co-workers reported a simple method for stereoselective synthesis of ( Z )-1-silyl-2-aryl-1,3-dienes ( 115 ) ( Scheme 30 ) [ 29 ]. This method used palladium-catalyzed silylstannylation of 4-(phenylselenyl)-but-1-yne ( 113 ) followed by oxidation-selenoxide elimination and Stille coupling.…”
Section: Silicon Dienesmentioning
confidence: 99%
See 1 more Smart Citation
“…Segi and co-workers reported a simple method for stereoselective synthesis of ( Z )-1-silyl-2-aryl-1,3-dienes ( 115 ) ( Scheme 30 ) [ 29 ]. This method used palladium-catalyzed silylstannylation of 4-(phenylselenyl)-but-1-yne ( 113 ) followed by oxidation-selenoxide elimination and Stille coupling.…”
Section: Silicon Dienesmentioning
confidence: 99%
“…The authors found that once the initial silylstannylation was completed the oxidation-selenoxide elimination and Stille coupling could be performed in either sequence with essentially identical overall yields for the sequence. Segi and co-workers reported a simple method for stereoselective synthesis of (Z)-1-silyl-2-aryl-1,3-dienes (115) (Scheme 30) [29]. This method used palladium-catalyzed silylstannylation of 4-(phenylselenyl)-but-1-yne (113) followed by oxidation-selenoxide elimination and Stille coupling.…”
mentioning
confidence: 99%